Symbolism in The Animated Film Raya and the Last Dragon - Sri Wulan; Nurhasanah; Nada Febriansyah Putri (ITScience (Information Technology and Science), 2022)
The aim of this study is to find out the major symbols in the animated film entitled Raya and the Last Dragon. The film presented lots of signs. This study focuses on the major symbols in the film. The major symbols are most frequently mentioned and presented in the film. They are considered representative symbols in the film. The major symbols were analyzed by the application of the qualitative approach. Five symbols are presented in this study. To begin with, the land of heart symbolically means the center of prosperity. The heart is considered the land of welfare. In addition, Kumandra means the land of harmony and peace. The people live harmoniously and peacefully with nature in Kumandra. Furthermore, Dragon’s Gem has also a symbolical meaning of unity. The gem gives a message of being united. Additionally, Sisu is the last dragon awakened by Raya, the protagonist. Sisu also gives a symbolic meaning of trust. Sisu teaches other characters to trust each other. Lastly, Drunn implies a symbolical meaning. It conveys the threat of sustainable development for humans and the environment. All in all, the five major symbols in the film contain meanings. Their meanings are the message of the film. Above and beyond, the five symbols give a message of living with unity, harmony, and peace with nature to maintain environmental sustainability. The five symbols as well prove reading a literary work is advantageous because the readers can be enlightened by the moral message of the literary work.